Revealing environmental inequalities embedded within regional trades. (10th August 2020) - Zhai, Mengyu; Huang, Guohe; Liu, Lirong; Xu, Xinli; Guan, Yuru; Fu, Yupeng
Abstract: Carbon emissions embodied in interprovincial trade (CEE-IT) are closely related with the environmental responsibility allocation. Besides the perspective of administrative division, more rational and effective clusters based on provincial characteristics is more conducive for understanding the regional emission reduction linkages and simplifying the steps of responsibility determination. To provide a reasonable management of CEs transference mitigation in China, this study develops a provincial clustering scale CEE-IT model through three-scale accountings (i.e., aggregated-scale, consumption-scale and income-scale analysis). Specifically, 30 provinces are aggregated into several new regions with similar characteristics. Carbon emissions from different energy sources are first considered to distinguish and specify different emission reduction modes. The input output analysis (IOA) and structural decomposition analysis (SDA) are applied to quantify the embodied interprovincial carbon emissions and the relative contributions of socio-economic factors at the sector-level of disaggregation and aggregation, respectively. Three-scale accountings are innovatively employed into EEBT model to deeply analyze the emissions along China's domestic inter-regional supply chains for identifying regional production, consumption and income-based emission responsibilities. Based on three accounting perspectives, the results provide suggestions for coordinated emission reduction across regions (including specific provinces) from the overall and decomposition levels. It shows that cutting the imports of mining sector for all regions could reduce emissions from the supply side. Rural household consumption and fixed capital formation are the major drivers for Ⅳ region from the consumption side. Technological innovations in Ⅲ region have reduced carbon emissions by 55.2% and contributed 159 Mt reductions from 2007 to 2012. Ⅲ region is insensitive to energy types and the utilization of crude oil in Ⅰ region limit the improvement of its system efficiency. Importing large quantities of emission-intensive products from Beijing and Jiangsu is a cause of high income-based emissions in Ⅱ region. Graphical abstract: Image 1 Highlights: Provincial clustering scale model for carbon transference mitigation in China is developed. Three-scale accountings are first applied to identify regional emission responsibilities. Provinces are aggregated into five new regions with similar characteristics. Spatial evolution characteristics of carbon transference between regions are evaluated. Interregional linkages are strengthened in the formulation of carbon mitigation policies.